An Algorithm to Analyze Cost Heterogeneity using Counterfactual Scenarios in Endovascular versus Open Repair of Abdominal Aortic Aneurysm: Predicting Costs for Subsequent Patients - Christopher A. Jones; Peter W. Callas; Robert W. Everett; Richard A. Galbraith; Richie Spitsberg; Jeffrey J. Petrozzino; Michael J. DeSarno; Andrew C. Stanley (Journal of Health Economics and Outcomes Research)
**Objectives:** We examined patient-specific predictors of high cost for endovascular (EVAR) and open (OPEN) repair of abdominal aortic aneurysm (AAA).